ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN PELAPORAN KEUANGAN MELALUI INTERNET FINANCIAL REPORTING (IFR) - Marhamah Marhamah; Penta Widyartati (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2023)
The internet is a communication network that functions to connect between electronic media quickly and precisely. The communication network will convey some of the information sent by transmitting signals with a frequency that has been adjusted for global standards in the use of the internet network It self using the Transmission Control Protocol/Internet Protocol. The company utilizes the internet as an appropriate financial reporting medium and is considered to be able to increase the effectiveness of the company's operations. Internet Financial Reporting (IFR) is voluntary disclosure of financial reports via the internet by companies. The application of IFR is carried out according to the company's objectives which are intended to increase the company's credibility. The positive impact of Internet Financial Reporting (IFR) is that the presentation of data in a timely and accurate manner is very useful for potential investors/investors in making investment decisions in companies. The research population for banking companies listed on the Indonesia Stock Exchange (IDX) for 2019-2021 was 43 companies. Using the purposive sampling method, a sample of 25 companies was obtained. The data used is secondary data from the Indonesia Stock Exchange (IDX) with multiple linear regression analysis method. The results of the analysis show that the leverage variable has a significant effect on Internet Financial Reporting (IFR), while the variables of profitability, auditor reputation, and company size have no effect on Internet Financial Reporting (IFR). Banking is expected to use Internet Financial Reporting (IFR) so that the public can see banking performance, especially in disclosing financial reports so that trust in banks is as good as possible.